2020
DOI: 10.1177/0022146520904373
|View full text |Cite
|
Sign up to set email alerts
|

The Two Faces of Diversity: The Relationships between Religious Polarization, Religious Fractionalization, and Self-rated Health

Abstract: A dominant discourse in the social sciences theorizes that religious diversity puts individuals’ health at risk via interreligious hostility. However, this discourse overlooks the different subtypes of religious diversity and the moderation of political institutions. To better understand the issue of diversity and health, in this study, we distinguish between two subtypes of religious diversity—polarization and fractionalization—and argue that their impacts on health are heterogeneous. Using a sample of 67,399… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 90 publications
0
15
0
Order By: Relevance
“…More importantly, religious diversity reflects the differences in religious beliefs and practices in a country. Lu and Yang 43 show that religious fractionalization is beneficial to self-rated health using survey data from 55 countries. They argue that diverse religious groups facilitate the accumulation of social capital toward one another, which benefits health and personal development.…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, religious diversity reflects the differences in religious beliefs and practices in a country. Lu and Yang 43 show that religious fractionalization is beneficial to self-rated health using survey data from 55 countries. They argue that diverse religious groups facilitate the accumulation of social capital toward one another, which benefits health and personal development.…”
Section: Resultsmentioning
confidence: 99%
“…In analyzing the American religious diversity, Heclo (2007) concluded that the diverse religious composition enabled an inclination toward tolerance and moderation in the USA. The moderating and liberating effects of religious fractionalization have been pointed out by many scholars (Lu and Yang, 2020;Montalvo and Reynal-Querol, 2005;Polletta and Jasper, 2001). For instance, Dorius and Firebaugh (2010) found that gender inequality declines across diverse religious and cultural traditions.…”
Section: Religious Fractionalizationmentioning
confidence: 99%
“…Accordingly, we define religious diversity as religious fractionalization by considering both the number and proportion of religious affiliations in a country. The religious fractionalization formula proposed by Herfindahl–Hirshman can effectively measure both the number and proportion of religious affiliations (Delhey and Newton, 2005; Grim and Finke, 2007; Lu and Yang, 2020; Patsiurko et al , 2012; Wuthnow, 2007; Yang and Ebaugh, 2001). where Sij is the share of religious affiliation i true(i=1 .. Ntrue) in country j.…”
Section: Religion: Religiosity Religious Affiliations Religious Fract...mentioning
confidence: 99%
See 1 more Smart Citation
“…They argue that the impact of religious diversity on different types of countries depends mainly on the efficiency of government institutions and that high religious diversity may lead to greater inter-communal tensions in countries with weak state systems, while in countries with better political systems it can have a positive impact on economic development and investment building [ 13 ]. Other studies of religious diversity have covered areas such as political economy [ 14 16 ], and biomedicine [ 17 ].…”
Section: Introductionmentioning
confidence: 99%